Uncertainty Across Volatility Regimes - Giovanni Angelini; Emanuele Bacchiocchi; Giovanni Caggiano; Luca Fanelli (Center for Economic Studies and ifo Institute (CESifo), 2017)
We propose a new non-recursive identification scheme for uncertainty shocks, which exploits breaks in the unconditional volatility of macroeconomic variables. Such identification approach allows us to simultaneously address two major questions in the empirical literature on uncertainty: (i) Does the relationship between uncertainty and economic activity change across macroeconomic regimes? (ii) Is uncertainty a major cause or effect (or both) of decline in economic activity? Empirical results based on a small-scale VAR with US monthly data for the period 1960-2015 suggest that (i) the effects of uncertainty shocks are regime-dependent, and (ii) uncertainty is an exogenous source of decline of economic activity, rather than an endogenous response to it.
Keywords: C32; C51; E44; G01; 330; heteroscedasticity; identification; non-recursive SVAR; uncertainty shocks; volatility regime